Arthroscopic triple arthrodesis for the patient with rheumatoid arthritis; a case report. (2nd January 2021) - Nakasa, Tomoyuki; Ikuta, Yasunari; Kanemitsu, Munekazu; Adachi, Nobuo
Abstract: We treated a 60 - year - old man with pes planovalgus due to rheumatoid arthritis. He had been suffering from left foot pain with swelling. Despite drug therapy, his foot pain and deformity had got worsen. Taking into consideration his skin and bone quality, arthroscopic triple arthrodesis was performed. To access the subtalar joint, 2 portals were applied at the sinus tarsi, and decortication was performed. For calcaneocuboid joint, 1.5 cm portal was applied along with joint line at calcaneocuboid joint. Calcaneocuboid joint was fully decorticated, then, 1.5 cm portal was applied at the joint line of talonavicular joint in parallel. Synovectomy and decortication under arthroscopy were performed. Once each joint was sufficiently prepared, it was fixed using screws via a percutaneous stab incision with an autologous bone graft from the iliac crest to the calcaneocuboid and talonavicular joint. At 12 weeks postoperatively, bone union was confirmed. The Japan Society for Surgery of the Foot (JSSF) RA foot and ankle scale had improved from the postoperative value of 38 points to a postoperative score of 86 points at one year. Plain radiographs showed that good alignment of the patient's hindfoot was maintained. We found that arthroscopic approach was able to achieve satisfactory outcome and minimise soft tissue trauma in a compromised patient.